Cutaneous plasmacytosis: Report of a Moroccan case!! - Naoufal Hjira; Noureddine Baba; Adil Boudhas; Abderrahmane Al Bouzidi; Mohammed Boui (Wolters Kluwer Medknow Publications, 2014)
Cutaneous plasmacytosis is a rare entity that has been reported almost exclusively in Asian countries and is usually seen in adult males. Primary cutaneous plasmacytosis clinically is characterized by multiple red-brown plaques and nodules typically located on the trunk. We report a case of a Moroccan 65-year-old man presented multiple infiltrated red plaques on the extremities and the trunk, the diagnosis of cutaneous plasmacytosis was retained without systemic involvement. To our knowledge, this is the first case of this type reported in a Moroccan adult man.